STRES, KOMPENSASI DAN KEPUASAN KERJA PADA KOMITMEN ORGANISASI DI KARYAWAN PT ROYAL KHORINDAH PURBALINGGA - Dian Safitri Koesoemasari; Rifky Kurniawan; Ratna Pujiastuti (Majalah Imiah Manajemen & Bisnis, 2021)
The study aims to test stress, compensation and job satisfaction on organizational commitment. The test is done with multiple linear regression. The results of this study prove that work stress has a positive effect is not significant, compensation has a significant negative effect and job satisfaction has no significant positive effect on organizational commitment. The results of this study provide an idea that stress and job satisfaction can affect organizational commitment even if it does not prove significant. Organizational commitment is strongly influenced by the compensation provided by the company. The study found that in developing countries such as Indonesia the level of one's basic needs greatly affects the organization's commitment. Employees will be tied to the organization if their basic needs are met. The results of this study are in accordance with Maslow's theory.